A hospital based cross sectional study on surgical profile of patients with chronic leg ulcers - Thakur, Archana L.; Chawada, Meghraj J.; Jamdade, P. T. (International Surgery Journal, 2020)
Background: Treatment of chronic leg ulcer is not easy. Appropriate diagnosis and proper treatment are the cornerstone for successful outcome. To study the profile of patients with chronic leg ulcers. Methods: Hospital based observational study was carried out in 108 cases. All patients coming to surgery OPD in our set up with chronic leg ulcers of duration of more than 6 weeks were advised admission if they were willing for the same. Then detailed history was recorded. Detailed examination of venous system was done for varicosities, incompetent perforators, sapheno-femoral or poplitio-femoral junction incompetence. In case of patient’s peripheral vascular diseases, detailed examination of arterial system was done. Descriptive statistics like frequencies and percentage for categorical data, mean and SD for numerical data has been depicted. Results: Majority of study subjects were in age range of 60 to 70 years. percentage of male patient (76.9%) was higher than that of the female (23.1%). 43.5% of participants with ulcer on left side and 56.5% participants had ulcer on right side. 47% of participants had complaints between 7 to 8 weeks. main etiological factor was infective etiology in 38.9% patients. 54.1% ulcers were found in lower 1/3rd of the leg. About 88.9% cases had positive culture. The most common organism grown was of pseudomonas in 45.8% cases. Conclusions: The most common etiology of chronic leg ulcer in this study is infective followed by traumatic ulcer. The most common associated condition found in chronic leg ulcer is diabetes mellitus.